Systematics of 12 Jurassic, Cretaceous, and Paleogene squat lobster taxa (Galatheoidea). (September 2022) - Klompmaker, Adiël A.; Robins, Cristina M.; Jakobsen, Sten L.; Sheldon, Emma
Abstract: Squat lobsters within Galatheoidea are very diverse with over 1, 300 extant species that live in all marine ecosystems, but their fossil record, starting in the Middle Jurassic, consists of only 200 species. Consequently, much remains to be learned about their biodiversity, phylogeny, and paleobiogeography. We describe five new species ( Galatheites sforum n. sp., Kimmeridgian, Late Jurassic, Germany; Vasconilia zapotitlanensis n. sp., Barremian, Early Cretaceous, Mexico; Eomunidopsis texcalaensis n. sp., Barremian, Early Cretaceous, Mexico; Protomunida bennickei n. sp., Danian, Paleocene, Denmark; and Protomunida eurekantha n. sp., Danian, Paleocene, Denmark) and one new genus ( Tethysgalathea n. gen., Ypresian, Eocene, Italy). We further reassign Munida cretacea (Albian, Early Cretaceous, Texas, USA) to Galathea?, return Eomunidopsis? cobbani (Campanian, Late Cretaceous, Colorado, USA) to its original genus, report on the second occurrence of Vetoplautus latimarginus Robins et al., 2013 (Tithonian, Late Jurassic, Czech Republic), and reinstate Palaeomunidopsis moutieri (middle Bathonian, Middle Jurassic, France) as the oldest galatheoid known to date. The five new species, all found in limestones containing corals, increase galatheoid diversity in the fossil record by 2.5%. Finally, the common yet hitherto unrecognized Protomunida eurekantha was discovered by making casts of external molds, revealing distinct spines on the posterior margin that are more difficult to see in internal molds and specimens with cuticle due to breakage. Collecting and studying the external molds for galatheoids and other fossil decapods could yield additional cryptic species. UUID: http://zoobank.org/68a25381-65c6-4773-a4f2-71d9b0a25304